KRITERIA PEMILIHAN LEMBAGA WAKAF DI INDONESIA: PENDEKATAN MULTICRITERIA DECISION MAKING - Rusydiana, Aam Slamet (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2018)
Islamic finance is also known as a social financial entity that also has an equally important role for public benefit. One of Islamic social financial instrument is waqf. Typically, waqf or endowments are managed by an institution known as nadzir or the management of waqf. This study tries to analyze the preferences and behavior of criteria for selection of waqf institution or nazhir waqf in Indonesia through the multicriteria decision making method known as Analytical Network Process (ANP) approach.The results conclude that the most priority criteria that influence the selection of waqf institution in Indonesia are financial transparency/accountability and innovative program. Therefore, waqf managers or nazhir must always be trustworthy and fully responsible for managing funds and endowments. In addition, professional and innovative managers are needed in managing waqf objects.